2019
DOI: 10.1177/0300060519862094
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation of deciduous tooth pulp into necrotic young permanent teeth for pulp regeneration in a dog model

Abstract: Objectives To investigate the potential for pulpal regeneration via autologous transplantation of deciduous tooth pulp into immature necrotic permanent teeth using an experimental dog model. Methods Experimental apical periodontitis was induced in 60 teeth of six Beagle dogs. Following canal disinfection and pulpotomy, autologous deciduous pulp tissue was transplanted into the root canals (n = 30); as controls, contralateral teeth were treated in accordance with the recommendations of the American Association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
0
13
0
2
Order By: Relevance
“…The studies that directly compared cell homing and cell transplantation [ 14 , 15 , 16 ] could not find a significant difference in apical healing [ 14 , 15 , 16 ]. Overall, the healing capacity seems to be sufficient in both techniques, as most of the lesions healed after treatment [ 14 , 15 , 16 ].…”
Section: Results Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that directly compared cell homing and cell transplantation [ 14 , 15 , 16 ] could not find a significant difference in apical healing [ 14 , 15 , 16 ]. Overall, the healing capacity seems to be sufficient in both techniques, as most of the lesions healed after treatment [ 14 , 15 , 16 ].…”
Section: Results Synthesismentioning
confidence: 99%
“…The studies that directly compared cell homing and cell transplantation [ 14 , 15 , 16 ] could not find a significant difference in apical healing [ 14 , 15 , 16 ]. Overall, the healing capacity seems to be sufficient in both techniques, as most of the lesions healed after treatment [ 14 , 15 , 16 ]. It seems apparent that the experimental groups (cell homing, cell transplantation) result in more apical healing than the control groups (no treatment) [ 16 ].…”
Section: Results Synthesismentioning
confidence: 99%
“…Vislumbrando, dessa maneira, a realização de um transplante autólogo da polpa, eliminando a necessidade de altos custos com manipulação e reprodução celular. Huang et al, 2019 investigaram o potencial de regeneração pulpar através de um transplante autólogo da polpa dentária de um dente decíduo em dentes permanentes necróticos imaturos de cães. O estudo concluiu que a implantação direta de tecido pulpar de dentes decíduos produz resultados clínicos, radiográficos e histológicos favoráveis.…”
Section: Discussionunclassified
“…Porém, a ascensão da nova técnica de autotransplante de polpa, seja ela decídua ou permanente, trouxe subsídios clínicos para diminuição do custo financeiro e operacional com o cultivo celular, eliminando esta etapa clínica da terapia regenerativa, além disso, apresentando protocolos aceitáveis para os pacientes em que nem mesmo extrações dentárias são necessárias. Além de seu alto potencial de aceitação pelos pacientes, a técnica de autotransplante trouxe excelentes resultados no que tange os parâmetros regenerativos do complexo dentino-pulpar (Cehreli et al, 2022;Feitosa et al, 2021;Huang et al, 2019).…”
Section: Discussionunclassified
“…Interest in stem cell therapies and regenerative medicines has grown notably over the last decade as their tremendous potential for effective treatments in a variety of medical diseases is being realized. Studies have shown that SHED are an ideal non-controversial and easily accessible cell source for use in regenerative medicine [ 15 , 16 , 17 , 18 ] The tissue regenerative effect of mesenchymal stem/stromal cells can be accomplished by the replacement of tissues with defects by differentiated dental MSCs/SCs themselves and/or through the induction of the de novo regeneration capacity of endogenous stem cells via remodeling of the stem cell niche [ 19 ].…”
Section: Introductionmentioning
confidence: 99%